Sociological Juridical Review Of Children Appointment Through The Determination Of Judges In The Religion Court Of Semarang - Isyadora Islami Salma; Rakhmat Bowo Suharto; Widayati Widayati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
This study aims to determine how the implementation process of adoptions that occurred in the Religious Court of Semarang, and what is the reason for the judge to give authority to the prospective adoptive parents. In answer to this problem the authors conducted a sociological juridical research, namely by conducting direct research and find data related to this study directly in the field, and also based on legislation regarding adoption. This is to obtain primary data and secondary data, using data collection techniques are observation, interview, and literature study. The data obtained in the analysis using qualitative analytical methods and presented descriptively.Based on the results of research that has been done in the Religious Court of Semarang, we can conclude that 1) the implementation of the adoption of the Religious Court of Semarang is done by people who are Moslem. Filing the petition has been set by the Religious Court of Semarang through 3 stages and was previously submitted to the Department of Social Welfare. 2) Determination of adoption set based on consideration of the judge with reference to the legislation and personal data information provided by the applicant.Keywords: Implementation; Adoption; Religious Court.